Analysis of Respondent Characteristics Regarding The Severity of Community-acquired Pneumonia Patients at Dr. H. Abdul Moeloek Hospital, Lampung. - Sanjaya, Rizki Putra; Herdato, M. Junus Didiek; Ajipurnomo, Adhari; Herliyana, Lina; Dilangga, Pad; Soeprihatini, Retno Ariza; Lyanda, Apri; Hendarto, Gatot Sudiro; Sinaga, Fransisca Tarida Yuniar; Kusumajati, Pusparini (Universitas Aisyah Pringsewu, 2025)
Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide, particularly among the elderly and immunocompromised patients. Various factors, including age, gender, bacterial pattern, comorbidities, and Pneumonia Severity Index (PSI) score, influence CAP severity. Understanding these characteristics is crucial for optimizing treatment strategies and predicting clinical outcomes. This descriptive-analytical cross-sectional study was conducted at Dr. H. Abdul Moeloek Hospital, Lampung, from December 2022 to January 2023. A total of 102 CAP patients were analyzed based on their age, gender, bacterial pattern, comorbidities, and PSI score. Data were processed using IBM SPSS 21.0, with Pearson correlation applied to assess relationships between variables. A statistically significant correlation was found between age and PSI score (p = 0.018), with a low-strength positive correlation (R = 0.234). This suggests that as age increases, CAP severity also increases (p = 0.011). However, no significant correlations were found between PSI score and gender, bacterial pattern, or diabetes mellitus. This study confirms that age is a significant factor influencing CAP severity, emphasizing the need for early screening and intervention in elderly patients. Although gender, bacterial pattern, and diabetes mellitus were not significantly correlated with CAP severity.